Determination of Stevioside and Rebaudioside A in Stevia Rebaudiana Leaves via preparative High Performance Liquid Chromatography (prep-HPLC) - Nurlin, Abu Samah; A.D.A., Hisham; S.A., Rahim (World Academy of Research and Publication, 2012)
Stevia rebaudiana leaves known as sweet leaf and it contain with non-caloric sweeteners (steviol-glycosides) whose consumption could exert beneficial effects on human health. In Malaysia, the applicable of steviol-glycosides was very limited. The sweetness of steviol-glycosides was about 300 times more than sugar produce from sugar cane. Nowadays, sugarcane has critical value due to its high consumptions in community. The objective of this study is to determine stevioside and rebaudioside A in Stevia Rebaudiana leaves qualitatively by using soxhlet extraction method analyzed via preparative HPLC. A series of standard solution for both stevioside and rebaudioside A were analyzed. Samples were sequentially extracted using methanol as the solvent and the column had been used in this study was Waters XBridge C18 column (150 mm x 4.6 mm I.D., 5µm). The mobile phase for C18 column performed in isocratic mode elution consisting of acetonitrile:water (80:20,v/v). Stevioside were the most abundant steviol-glycosides (Rt = 4.23 min) found in stevia rebaudiana leaves samples followed by rebaudioside A (Rt = 4.28 min). The objective of analysis was achieved and this leads to the suggestion of using the Capcell Pak C18 – MGII Column (250 mm x 4.60 mm ID, 5 µm) as the replacement to the C18 column that was used in this study. Also, it is a good practice if the sample was extracted using solid phase extraction method compare to the conventional practice using sohxlet extraction method.